URINARY TRACT INFECTION IN NEONATES - Mojca Kavčič; Maša, Koce; Minca Mramor; Nina Battelino (Slovenska pediatrija, 2023)

(untitled)
Urinary tract infections occur more often in newborns than in older children. In the former edition of this journal, dr. Kavčič et al. published the results of their retrospective analysis of 274 newborns hospitalized at the Neonatology department of the University Children’s Hospital Ljubljana between 2013 and 2021 and who were diagnosed with urinary tract infections. They present the basic information about urinary tract infection in newborns, as well as the clinical signs, the most common pathogens, treatment, the percentage of newborns with congenital anomalies of the kidney and urinary tract, as well as antibiotic resistance in the Slovenian cohort of newborns. Therefore, in the present edition, dedicated to the 6th Slovenian Symposium of Pediatric Nephrology, the subject is not presented again.